2013
DOI: 10.1369/0022155413477114
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Approach to Detect Gap Junction Plaques and Associate Them with Cells in Fluorescent Images

Abstract: Fundamental to understanding how tissues function is understanding how the cells that compose them communicate. In most tissues and organs, cells do not exist as homotypic monolayers but rather coexist as multiple different cell types in close proximity to one another. In some cases, these relationships are random and have no functional significance; others are symbiotic, where the presence and proximity of a neighboring cell are vital to another cell's quiescence, specification, maturation, function, survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To evaluate the expression of Cx proteins in NSCs in the murine SVZ, we first labeled the NSCs using a BrdU-labeling protocol in which label-retaining cells (LRCs) represent qNSCs. 34 We found that a percentage of SVZ LRC-NSCs express multiple Cx proteins, and a higher percentage of LRC-NSCs express Cx43 ( Figure 2B ), like ECs. To determine whether Cx43 is present between NSCs and ECs in the SVZ in vivo , we performed immunohistochemistry and high-resolution confocal imaging of SVZ coronal sections.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…To evaluate the expression of Cx proteins in NSCs in the murine SVZ, we first labeled the NSCs using a BrdU-labeling protocol in which label-retaining cells (LRCs) represent qNSCs. 34 We found that a percentage of SVZ LRC-NSCs express multiple Cx proteins, and a higher percentage of LRC-NSCs express Cx43 ( Figure 2B ), like ECs. To determine whether Cx43 is present between NSCs and ECs in the SVZ in vivo , we performed immunohistochemistry and high-resolution confocal imaging of SVZ coronal sections.…”
Section: Resultsmentioning
confidence: 77%
“…Quantification of connexin protein colocalization with LRCs or ECs was performed on confocal z stack images by a computational approach using FARSIGHT for nuclear segmentation and MATLAB. 34 …”
Section: Methodsmentioning
confidence: 99%
“…Using immunohistochemistry and antibodies against different Cx proteins and CD31, which is expressed by all ECs, we found a low percentage of ECs expressing Cx26 and Cx31, while a high percentage of ECs express Cx43 ( Figure 2a ). To evaluate the expression of Cx proteins in NSCs in the murine SVZ, we first labeled the NSCs using a BrdU-labeling protocol in which label-retaining cells (LRC) represent quiescent NSCs 33 . We found that a percentage of SVZ LRC-NSCs express multiple Cx proteins, and a higher percentage of LRC-NSCs express Cx43 ( Figure 2b ), similar to ECs.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, wild-type mice received BrdU (7.5mg/ml) i.p injections twice daily for 5 days and sacrificed 4 wk after the last injection. Quantification of connexin protein colocalization with LRCs or ECs was performed on confocal z-stack images by a computational approach using FARSIGHT for nuclear segmentation and MATLAB programs as previously published in the lab 33 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation